Alternative Dispute Resolution (ADR) in Nepal: Legal Framework, and Practices - Yadav, Prabin Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2024)
In Nepal, dispute resolution has typically depended on a mix of traditional methods and modern legal structures. Alternative dispute resolution (ADR) techniques, including negotiation, arbitration, conciliation, and mediation, have grown in importance throughout time alongside traditional court proceedings, providing parties with more effective and flexible options for resolving disputes outside of the courtroom. Panchayats and Panchalis, two community-based systems, served as the foundation for Nepal’s conflict resolution procedures in the past. However, ADR has developed into a more organised and approachable procedure as a result of the passing of legislation like the Arbitration Act of 2055. Since ADR may provide justice in a timely and economical manner, the judiciary actively encourages it. The legislative frameworks, which include the Foreign Investment and Technology Transfer Act and the Development Board Act, offer a methodical approach to resolving issues through alternative dispute resolution (ADR), guaranteeing that parties have access to options including arbitration and mediation for effective dispute resolution. A well-known case like Rajendraman Sherchan v. Appellate Court and National Construction Company Appellate Court have helped to clarify ADR principles, especially in commercial disputes, supporting the legitimacy of ADR outcomes and encouraging the adoption of alternative dispute resolution practices.